Enzymatic amplification of a Y chromosome repeat in a single blastomere allows identification of the sex of preimplantation mouse embryos. - Bradbury, M W (1990)
The polymerase chain reaction (PCR) technique has been adapted to identify the sex of preimplantation mouse embryos rapidly. PCR was used to amplify a specific repeated DNA sequence on the Y chromosome from a single isolated blastomere in under 12 hr. The remainder of the biopsied embryo was then transferred to a pseudopregnant female and carried to term. Using this technique, 72% of embryos can be classed as potentially either male or female. Transfers of such embryos have produced pregnancies with 8/8 fetuses (100%) being of the predicted sex. Variations of the technique have demonstrated certain limitations to the present procedure as well as indicated possible strategies for improvement of the assay. The PCR technique may have wide application in the genetic analysis of preimplantation embryos.